SMEs, Employment Generation, and Islamic Finance - Azam, Md Siddique E; Abdullah, Moha Asri (Universitas Muhammadiyah Yogyakarta, 2024)
Almost wherever the economy is growing, small and medium-sized businesses (SMEs) are the ones doing the heavy lifting. Who are these SMEs? How does the definition of SME differ across different countries? What are the contributions of SMEs in terms of employment and GDP? How can Islamic finance play a significant role in scaling up the business performance of SMEs and, subsequently, their contribution to employment and the economy? What are the issues and challenges faced by SMEs and Islamic finance that would resolve into greater employment generation? Addressing all these questions, this paper provides an overview of SMEs globally and their definitions in different countries as well as in Malaysia. Simultaneously, some issues and challenges are discussed. Furthermore, the paper presents Islamic finance as a better solution to the financial accessibility of SMEs in future economic activities. The paper thus attempts to illustrate a model or framework that would work well for SMEs to generate productive employment opportunities in their respective economies. To achieve the objectives of this paper, secondary data was used to present all the statistical figures and tables. For any generalizations, recommendations, or conclusions, an extensive review of literature from various sources was conducted.